Employer-Based Interventions for Schizophrenia: A Systematic Literature Review and Psychiatric Nursing Perspective - Siti khadijah; Endang Caturini Sulistiyowati; Dwi Ariani Sulistyowati; Abdul Ghofur; Sarka Ade Susana (Institut Kesehatan Suaka Insan, 2026)
Employment is crucial for the recovery and social inclusion of individuals with schizophrenia and other severe mental illnesses (SMI), yet significant barriers to competitive employment persist. Although various employer-based vocational interventions have been developed, their efficacy remains variable across settings. Guided by the PRISMA framework, this systematic review evaluates the effectiveness of employer-based interventions in improving employment outcomes for this population. A comprehensive search of Scopus, Web of Science, and PubMed was conducted for studies published between 2020 and 2026. Following rigorous screening, 19 studies from nine countries were selected for qualitative synthesis. The interventions assessed included Individual Placement and Support (IPS), Supported Employment (SE), integrated vocational-psychiatric programs, and return-to-work initiatives. Results indicate that IPS and SE consistently provide the strongest evidence for improving competitive employment rates, job acquisition, and job retention, with one study reporting a 7.5% increase in job availability post-SE implementation. Conversely, interventions relying exclusively on employer-directed communication demonstrated limited efficacy. In conclusion, IPS and Supported Employment are the most effective strategies for enhancing employment outcomes in this population. Integrating vocational support with comprehensive mental health services is critical for fostering sustainable employment and facilitating long-term recovery.